Impact of the COVID-19 pandemic on the routine immunization system in Bangladesh - Md. Tanvir Hossen; Md Sayik Bin Alam; Md. Sahidul Islam; Emanuele Montomoli; Ralf Clemens; Sue Ann Costa Clemens; Mohammad Delwer Hossain Hawlader; Md Foyjul Islam (PLoS ONE, 2025)
The COVID-19 pandemic has put immense pressure on countries’ health structures to maintain routine immunization and VPD surveillance programs, especially in LMICs such as Bangladesh. Understanding the effects of COVID-19 will allow countries like Bangladesh to become better prepared for future health emergencies, so this study explored the effects of COVID-19 on routine immunization and VPD surveillance programs in Bangladesh. With a sequential mixed-method approach, the quantitative data was collected from the DHIS2 for January 2019-December 2021. The qualitative data was collected from ten KIIs, which was conducted with the key stakeholders of EPI and VPD surveillance in Bangladesh. Findings suggest that there had been three drop-rebound periods in the routine immunization program in Bangladesh. The study identified that Bangladesh was able to catch up with the pre-pandemic level immunization within four to six months from the first drop, and the immunization drops became less severe with the progression of time. COVID-19-related movement restrictions, lack of workforce, fear and concern regarding COVID-19, prioritizing COVID-19 vaccination, lack of a comprehensive EPI structure in urban compared to rural areas, and lack of knowledge to conduct EPI and VPD activities amidst the pandemic situation were identified as the main reasons for these drops.